Globalization and Africa: implications for human development - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2012)
Purpose The purpose of this paper is to assess the effects of trade and financial globalization on human development in 52 African countries using updated data (1996-2010) and a new indicator of human development (adjusted for inequality). Design/methodology/approach The estimation technique used is a Two-Stage-Least Squares Instrumental Variable methodology. Instruments include: income-levels, legal-origins and religious-dominations. The first-step consists of justifying the choice of the estimation technique with a Hausman-test for endogeneity. In the second-step, we verify that the instrumental variables are exogenous to the endogenous components of explaining variables (globalization dynamic channels) conditional on other covariates (control variables). In the third-step, the strength and validity of the instruments are assessed with the Cragg-Donald and Sargan overidentifying restrictions tests respectively. Robustness checks are ensured by: (1) use of alternative globalization indicators; (2) endogeneity based estimation; (3) adoption of two interchangeable sets of instruments; (4) estimation with a technique that controls for time-invariant unobservable shocks that affect openness and human development simultaneously. Findings Findings broadly indicate that while trade globalization improves human development (consistent with the neoliberal theory), financial globalization has the opposite effect (in line with the hegemony thesis). The 'life expectancy' component of the HDI weighs most in the positive impact of trade globalization on human emancipation. Practical implications Capital accounts should be opened in tandem with financial and institutional development. The investment atmosphere needs improvement to curtail capital flight (about 39%). Other policy implications include: adoption of openness options in a selective and gradual manner, development of some industrial backbone for an import-substitution or export-led industry, emphasis on regional trade and building capacity, development of the agricultural sector with continuous government assistance, building of rural infrastructure, increasing adult literacy rate and developing human resources, fighting corruption and mitigating wastages in government expenditure. Originality/value These findings are based on very recent data. Usage of the inequality adjusted human development index first published in 2010, corrects past works of the bulk of criticisms inherent in the first index.
Keywords: F10; F30; I10; I30; O55; 330; Globalization; Human development; Africa